Pengaruh Media Pembelajaran Monopoli terhadap Kreativitas dan Hasil Belajar Siswa Posisi Strategis di SMAN 1 Sutera - Siti Nurhaliza; Sri Mariya (Asian Journal of Islamic Studies and Da'wah, 2026)
The development of engaging and interactive instructional media is necessary to support students’ understanding of the topic of Indonesia’s strategic position at the senior high school level. This study aimed (1) to implement Monopoly game–based instructional media for the topic of Indonesia’s strategic position in Grade XI Phase F at SMAN 1 Sutera and (2) to analyze the influence of Monopoly media on students’ creativity and learning outcomes. A quantitative method with a quasi-experimental design was employed, involving an experimental class using Monopoly media and a control class receiving conventional instruction. Data were analyzed using JASP v0.95.4 through a series of validity, reliability, normality, and homogeneity tests. Students’ creativity was analyzed using an independent-samples t-test, while learning outcomes were analyzed using the non-parametric Mann–Whitney test. The results show that (1) the implementation of Monopoly-based instructional media proceeded well and received positive responses from students; (2) Monopoly media had a significant effect on students’ creativity, with a p-value of 0.012 and a t-value of 2.572; and (3) Monopoly media had a significant effect on learning outcomes, as indicated by a higher normalized gain score in the experimental class (0.70, medium category) compared with the control class (0.28, low category), as well as a U-value of 1128. These findings confirm that the use of Monopoly-based instructional media can enhance students’ creativity and learning outcomes on the topic of Indonesia’s strategic position.